2006
DOI: 10.1111/j.1365-2958.2006.05394.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation of active inclusion bodies in the periplasm of Escherichia coli

Abstract: SummaryTo examine the relationship between folding and aggregation in the periplasm of Escherichia coli, we have analysed the cellular fates of exported proteins fused to either the wild-type maltose-binding protein (MalE) or the aggregation-prone variant MalE31. The propensity of fusion proteins to aggregate in the periplasm was determined by the intrinsic folding characteristics of the upstream protein. When b-lactamase or alkaline phosphatase was linked to the C-terminus of MalE31, the resultant fusion prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 41 publications
2
70
0
1
Order By: Relevance
“…This differential centrifugation procedure was mandatory for the global analysis of periplasmic protein aggregates. It missed, however, a fraction of periplasmic protein aggregates that had already pelleted during the first centrifugation step (27). 4,5 For the analysis of MalE, OppA, HisJ, and MglB, samples were centrifuged for 10 min at 20,000 ϫ g immediately after the spheroplasting procedure, and supernatants containing the periplasmic soluble proteins were withdrawn.…”
Section: Methodsmentioning
confidence: 99%
“…This differential centrifugation procedure was mandatory for the global analysis of periplasmic protein aggregates. It missed, however, a fraction of periplasmic protein aggregates that had already pelleted during the first centrifugation step (27). 4,5 For the analysis of MalE, OppA, HisJ, and MglB, samples were centrifuged for 10 min at 20,000 ϫ g immediately after the spheroplasting procedure, and supernatants containing the periplasmic soluble proteins were withdrawn.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with recent findings of Betton and coworkers who showed that despite its poor folding efficiency in the periplasm, a fusion of MalE31-Bla retained some catalytic activity. 29 Our previous findings showed that MalE31 expressed in the cytoplasm is somewhat soluble, albeit to a lesser extent than wt MBP. 22 It has been shown that the periplasmic chaperone FkpA can decrease aggregation of MalE31, whereas another periplasmic chaperone SurA did not affect MalE31 aggregation.…”
Section: Cis-and Trans-acting Factors That Affect Protein Folding In mentioning
confidence: 99%
“…For these studies, we used E. coli MBP and a collection of MBP variants that become kinetically trapped in offpathway intermediates that are prone to aggregation. 29 One of these, a double mutant called MalE31 (G32D/I33P), reportedly forms inclusion bodies in the periplasmic space. 45 We cloned four different Fig.…”
Section: Cis-and Trans-acting Factors That Affect Protein Folding In mentioning
confidence: 99%
See 1 more Smart Citation
“…Only coexpression of multiple cytosolic chaperones (DnaK, DnaJ, GrpE, GroES, and GroEL) combined with expression at room temperature and lower concentrations of the inducer, IPTG (isopropyl beta-D-thiogalactoside), resulted in reasonable levels of soluble cytosolic expression and bioactivity comparable to native IL-6. 69 Even though there have been some successful attempts to produce disulfide-bonded proteins in E. coli using various strategies 70 other than the multiple chaperone approach required for IL-6, some of these attempts have unexpectedly resulted in the production of periplasmic inclusion bodies 71 and expression of proteins with nonnative disulfide bonds, 72 as was most likely the case for IL-6. 69 Thus, the limitations of E. coli for the expression of human proteins can be overcome but only by testing multiple expression conditions, including localization and coexpression of chaperones.…”
Section: Expression Hosts For Soluble Targetsmentioning
confidence: 99%